The Influence of Ownership Structure on the Financial Performance of Banks - Sigit Pamungkas; Muchtar Hidayat; Muhammad Syarif; Farah Margaretha Leon; Henny S. Lestari (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze the effect of ownership structure on the financial performance of banks in Indonesia. The variables considered include managerial, institutional, foreign, and public ownership. The study also examines bank size and credit risk as control variables, with financial performance measured by Net Interest Margin (NIM), Return on Assets (ROA), and Return on Equity (ROE). The method used is panel data regression, employing a purposive sampling technique on 43 banks listed on the Indonesia Stock Exchange during the 2019-2023 period. The study results indicate that managerial, institutional, and public ownership variables do not have a significant effect on financial performance, while foreign ownership has an impact on ROE. Additionally, bank size and credit risk are shown to affect both ROA and ROE. These findings suggest that factors beyond ownership structure play a more significant role in determining the financial performance of banks in Indonesia.